ANALISIS DAMPAK EKONOMI WISATA BAHARI TERHADAP PENDAPATAN MASYARAKAT LOKAL (Studi Kasus Ombak Bono Sungai Kampar Kabupaten Pelalawan Provinsi Riau) - Saputra, Rico; Iyan, Ritayani; ', Mardiana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study was to identify the characteristics of the work, the cost incurred society since their attraction Bono waves and analyzing the economic impact caused by the activities of local community-based nature of the public revenues attractions Kampar river. The method used in this research is descriptive analysis. The results showed that before the existence of attraction waves Bono work is dominated by agriculture, but after attractions waves Bono a lot of work in the field of trade, an increase in infrastructure such as access roads, as there are many lodging or hotels and restaurants. With the development does attractions waves Bono certainly a positive effect on income for the community around the area, the more the number of tourists who come will certainly affect the income of society that can take advantage of this opportunity, especially merchants.Keywords: Economic Impact, Marine Tourism, Revenue, and Local Communities